An antibiotic-overproducing mutant of Streptomyces granaticolor with impaired differentiation - Stastná, J; Blumauerová, M; Janda, I; Ludvík, J; Cáslavská, J (Journal of basic microbiology, 1987)
A thy- tetracycline-resistant mutant of Streptomyces granaticolor was prepared by mutagenesis of the parental strain ETH 7437. The mutant exhibits a different morphology and an overproduction of granaticins. The ability to form an aerial mycelium and spores has been lost. The mutant cells have a round or an atypical shape and a thick cell wall, the membraneous system is enlarged by numerous mesosomes. Division septa are formed rarely. The mutant is more sensitive to both low and high temperature than the parental strain. The altered features are stably maintained for many generations. Ribosomal proteins of the mutant do not differ substantially from those of the original strain indicating that the mutant phenotype is not due to an alteration at the translational level.
Keywords: Temperature; rezistence na tetracyklin; mutace; protinádorová antibiotika; Ribosomal Proteins; Streptomyces; naftochinony; elektroforéza v polyakrylamidovém gelu; fermentace; elektronová mikroskopie; chromatografie na tenké vrstvě; ribozomální proteiny; Electrophoresis, Polyacrylamide Gel; Tetracycline Resistance; Microscopy, Electron; Antibiotics, Antineoplastic; Fermentation; Naphthoquinones; teplota; Mutation; Chromatography, Thin Layer